Pengaruh Gaya Hidup, Etnosentrisme Konsumen, Kualitas Produk Terhadap Keputusan Pembelian Melalui Minat Beli: (Studi pada Konsumen Hamzah Batik Malioboro) - Zaezatun , Agustyaning; Rimiyati , Hasnah (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
This study aims to analyze the effect of lifestyle, consumer ethnocentrism and product quality on purchasing decisions through buying interest. The subjects in this study were consumers of Hamzah Batik Malioboro who had purchased Hamzah Batik Malioboro products at least once. This research was conducted with a total sample of 185 respondents who were determined by using a non-probability sampling technique using purposive sampling and distributing questionnaires to respondents using Google Form. The analytical tool in this study uses Structural Equation Modeling (SEM) with the AMOS version 23 application program. The results of this study indicate that Lifestyle has no positive and significant effect on purchasing decisions for Hamzah Batik products. Consumer ethnocentrism and product quality have a positive and significant effect on purchasing decisions for Hamzah Batik products. Buying interest has a positive and significant effect on purchasing decisions for Hamzah Batik products. Lifestyle, consumer ethnocentrism and product quality have a positive and significant impact on purchasing decisions mediated by interest in buying Hamzah Batik products.